2021
DOI: 10.1111/syen.12472
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the nonadaptive radiation of an ancient lineage of ground‐dwelling stick insects (Phasmatodea: Heteropterygidae)

Abstract: Stick and leaf insects (Phasmatodea) are large terrestrial herbivorous arthropods known for masquerading as plant parts such as bark, twigs and leaves. Their evolutionary history is largely shaped by convergent evolution associated with adaptive radiations on geographically isolated landmasses that have repeatedly generated ground‐dwelling ecomorphs. The members of one lineage, however, the Oriental Heteropterygidae, are morphologically rather uniform, and have a predominantly ground‐dwelling lifestyle. The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 92 publications
(242 reference statements)
4
50
0
3
Order By: Relevance
“…1 – 5 ). The outgroup taxa adapted from Bank et al 26 were found to present a similar topology with minor differences in regard to weakly supported sister group relationships (Supplementary Fig. 1 ).…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…1 – 5 ). The outgroup taxa adapted from Bank et al 26 were found to present a similar topology with minor differences in regard to weakly supported sister group relationships (Supplementary Fig. 1 ).…”
Section: Resultsmentioning
confidence: 80%
“…Adapted to a tree-dwelling life style, phylliid masquerade is achieved by simulating the broad leaves of flowering plants and the additional imitation of the diffuse growth of leaf veins in the female forewing venation 19 that has perfected their cryptic appearance in the foliage. This uniform adaptation is best described as a nonadaptive radiation in which the diversification was not accompanied by relevant niche differentiation 50 , resulting in taxa with little or no ecological and phenotypic variation 51 , as has been recently suggested for a clade of uniformly ground-dwelling stick insects 26 . Both the broad leaf habitus and the net venation of Phylliidae are evidently linked to the eudicot angiosperm evolution.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Stick and leaf insects are an impressive model group for the exploration of many evolutionary aspects, especially convergence. Limited spatial dispersion and extensive adaptive radiation led to a high degree of convergent traits in Phasmatodea, (e.g., in terms of visual camouflage [184][185][186][187], oviposition techniques [109,[188][189][190][191][192][193][194], different degrees of wing loss [195][196][197], and ecomorphs (morphological forms with similar ecological occupancy) with specific vertical stratification within the vegetation [108,198,199]). Phasmids are predominantly nocturnal insects that are distributed nearly worldwide and exceptionally herbivorous [184][185][186][187]194,200], with the highest diversity in the tropics.…”
Section: Stick Insects and Their Adhesive Systemsmentioning
confidence: 99%